Literature Review of Research Trend of Ethnoscience-Infused Teaching Materials in Elementary IPAS Learning in 2020-2025 - Esti Ayu Ratnasari; Ani Rusilowati; Diana Diana; Bambang Subali; Nuni Widiarti (Universitas Negeri Semarang, 2024)
The rapid development of the times, including in the world of education, requires innovation in learning. One of the innovations that can be made is related to teaching materials and collaborating with ethnoscience. Ethnoscience is a learning that integrates culture into it as part of the learning process. The writing of this article aims to find out the research trends of ethnoscience-laden teaching materials in IPAS subjects in elementary schools. The research method used is a systematic literature review (SLR). The analysis was conducted on 15 articles indexed by Google Scholar from 2020 to 2025. The results showed that (1) The trend of research on ethnoscience-based teaching materials continues to increase every year, (2) The university that conducts the most research on ethnoscience-based teaching materials is Mataram University, (3) The learning model applied in the research is problem-based learning (PBL) and project-based learning (PjBL), (4) There are various cognitive abilities of students that can be developed with ethnoscience-loaded teaching materials, (4) IPAS material that dominates in research is human digestion material, heat transfer, and motion and force, (5) Making ethnoscience-loaded teaching materials is developed through various applications or software.